Case Report: Novel Monitoring for Anaerobic Conditions Detected by Respiratory Quotient in a Critically Ill Pediatric Patient - Hayashi, Kenichiro; Matsui, Hikoro (Frontiers in Pediatrics, 2022)
Background Hyperlactemia after cardiopulmonary bypass is associated with adverse events during the early postoperative period in children. Serum lactate levels, a standard marker of anaerobic metabolism, are determined by the production, conversion and clearance of lactate, and may lag behind the anaerobic response. Here, we report a neonatal case under anaerobic conditions after cardiac surgery, whose expired gas parameters dramatically changed before a rise in blood lactate. Case Presentation A 23-day-old girl with tetralogy of Fallot was admitted to the pediatric intensive care unit after modified Blalock-Taussig shunt operation. As hemoconcentration increased and pleural fluid and ascites accumulated, we performed partial exchange transfusion to prevent shunt occlusion. Ten minutes after partial exchange transfusion, oxygen uptake and carbon dioxide production measured by indirect calorimetry suddenly dropped, while the respiratory quotient began to rise steeply before hyperlactatemia developed a few hours later. Conclusion Analysis of expired gas in critically ill children can detect the transition from aerobic to anaerobic conditions before hyperlactatemia.